The Influence of languange Policy on Indonesian Languange in Secondary School and Teacher Perception - Hakubun, Yohanis; Marlen Wariunsora (Asosiasi Ide Bahasa Kepri, 2024)
This study aims to analyze the influence of language policy on Indonesian language teaching in secondary schools and teachers' perception of the policy. Language policy plays an important role in shaping the curriculum and teaching methods, especially in Indonesian subjects which have a central role in the formation of national identity. This research method uses a qualitative approach. by combining surveys and in-depth interviews to explore teachers' views on language policy and its application in daily learning. The results showed that most teachers responded positively to the policy, despite challenges in implementation, such as a lack of training and resources. These findings provide important insights for policymakers to improve language policies and provide better support for teachers in implementing these policies.